Direct covalent attachment of silver nanoparticles on radical-rich plasma polymer films for antibacterial applications. Issue 37 (6th August 2018) - Akhavan, Behnam; Bakhshandeh, Sadra; Najafi-Ashtiani, Hamed; Fluit, Ad C.; Boel, Edwin; Vogely, Charles; van der Wal, Bart C. H.; Zadpoor, Amir A.; Weinans, Harrie; Hennink, Wim E.; Bilek, Marcela M.; Amin Yavari, Saber
Abstract : Ion-assisted plasma polymerization for single-step, covalent immobilization of silver nanoparticles on surfaces. Abstract : Prevention and treatment of biomaterial-associated infections (BAI) are imperative requirements for the effective and long-lasting function of orthopedic implants. Surface-functionalization of these materials with antibacterial agents, such as antibiotics, nanoparticles and peptides, is a promising approach to combat BAI. The well-known silver nanoparticles (AgNPs) in particular, although benefiting from strong and broad-range antibacterial efficiency, have been frequently associated with mammalian cell toxicity when physically adsorbed on biomaterials. The majority of irreversible immobilization techniques employed to fabricate AgNP-functionalized surfaces are based on wet-chemistry methods. However, these methods are typically substrate-dependent, complex, and time-consuming. Here we present a simple and dry strategy for the development of polymeric coatings used as platforms for the direct, linker-free covalent attachment of AgNPs onto solid surfaces using ion-assisted plasma polymerization. The resulting coating not only exhibits long-term antibiofilm efficiency against adherent Staphylococcus aureus ( S. aureus ), but also enhances osteoblast adhesion and proliferation. High resolution X-ray photoelectron spectroscopy (XPS), before and after sodium dodecyl sulfate (SDS) washing, confirms covalent bonding. The development of such silver-functionalized surfaces through a simple, plasma-based process holds great promise for the fabrication of implantable devices with improved tissue-implant integration and reduced biomaterial associated infections.